Balancing "Critique for Improvement" With "Critique for Emancipation" in Management Learning and Education. (June 2022) - Wallo, Andreas; Martin, Jason; Sparrhoff, Gun; Kock, Henrik
Promoting the capacity for critical reflection is a pivotal part of management learning and education. Based on the concept of developmental learning, the purpose of this paper is to explore and outline two types of critical reflection: critique for improvement and critique for emancipation . Critique for improvement is based on a performative intent and is aimed at using critical reflection to improve organizational practices. Critique for emancipation is based on a critical performative intent and focuses on emancipation from repressive ideological and social conditions that place unnecessary restrictions on the development of human consciousness. In this paper, it is argued that managers and leaders enrolled in management education need to be exposed to both critique for improvement and critique for emancipation. A heuristic conceptual framework is therefore proposed, along with strategies for how to balance the two types of critique in management learning and education and propositions to be explored in further research.